Gambaran Efektivitas Ubi Jalar Ungu Sebagai Media Alternatif Pertumbuhan Jamur Aspergillus Flavus Dengan Metode Rebus Dan Ekstrak - Fitri Ayu Wulandari; Rizki Perdani; Sri Suhartati; Hajrah Hidriya (Politeknik Unggulan Kalimantan, 2025)
The high cost and limited availability of synthetic media such as Sabouraud Dextrose Agar (SDA) have prompted the need for alternative, natural-based media that are more affordable and readily available. This study aims to determine the effectiveness of purple sweet potato (Ipomoea batatas L. Poir) as an alternative growth medium for Aspergillus flavus using boiling and extract preparation methods. The study was conducted experimentally using purple sweet potato concentrations of 10%, 20%, 30%, 40%, and 50%, with SDA serving as the control. Fungal growth was observed macroscopically (colony diameter) and microscopically over six days. Data were analyzed using the Kruskal-Wallis test and Post Hoc Mann-Whitney test. The results showed that purple sweet potato media can serve as an alternative medium due to its rich nutrient content, including carbohydrates, vitamins, minerals, and especially anthocyanins, which support fungal growth. Based on the findings and statistical analysis, it can be concluded that the boiling method at concentrations of 40%–50% is more optimal and effective as an alternative growth medium for Aspergillus flavus (p = 0.686).